Settlement of Criminal Offences Based on Victim Recovery and Protection Through the Village Krama Assembly (A Study in Sesait Village, North Lombok District) - Nirmala, Atika Zahra; Rahmania, Nunung; Taufik, Zahratul'ain (Unram Law Review, 2024)
This research aims to explore the case settlement mechanism through MKD, specifically examining the forms of recovery and victim protection provided by MKD. This empirical legal study adopts a socio-legal approach and employs case studies. The findings reveal that the criminal case resolution process through MKD starts with a report, followed by verification and the scheduling of a meeting by MKD. A mediation process then takes place, where if the parties agree to reconcile, MKD drafts a peace deed. If not, minutes are prepared, and MKD advises the parties to pursue formal legal channels. In terms of victim recovery and protection, particularly in domestic violence cases, during mediation, the victim is kept separate from the perpetrator to prevent further violence, intimidation, or third-party intervention. Should reconciliation be reached, a peace deed is drawn up, stipulating that if the perpetrator repeats their actions, litigation will follow immediately. This approach serves to deter future offenses and safeguard victims. Given the Sesait village community's strong adherence to customary law, perpetrators who sign a peace deed are also subject to traditional sanctions imposed by tau loka empat. These sanctions aim to restore relationships between the parties and reintegrate harmony within the community. The sanctions not only reduce the stigma surrounding the perpetrator but also provide support to the victim. Thus, the recovery concept in the Sesait community extends beyond the victim to include the perpetrator and the broader community.